Cross-sectional and prospective relationships of passive and mentally active sedentary behaviours and physical activity with depression. (August 2020) - Hallgren, Mats; Nguyen, Thi-Thuy-Dung; Owen, Neville; Stubbs, Brendon; Vancampfort, Davy; Lundin, Andreas; Dunstan, David; Bellocco, Rino; Lagerros, Ylva Trolle
Abstract : Background: Sedentary behaviour can be associated with poor mental health, but it remains unclear whether all types of sedentary behaviour have equivalent detrimental effects. Aims: To model the potential impact on depression of replacing passive with mentally active sedentary behaviours and with light and moderate-to-vigorous physical activity. An additional aim was to explore these relationships by self-report data and clinician diagnoses of depression. Method: In 1997, 43 863 Swedish adults were initially surveyed and their responses linked to patient registers until 2010. The isotemporal substitution method was used to model the potential impact on depression of replacing 30 min of passive sedentary behaviour with equivalent durations of mentally active sedentary behaviour, light physical activity or moderate-to-vigorous physical activity. Outcomes were self-reported depression symptoms (cross-sectional analyses) and clinician-diagnosed incident major depressive disorder (MDD) (prospective analyses). Results: Of 24 060 participants with complete data (mean age 49.2 years, s.d. 15.8, 66% female), 1526 (6.3%) reported depression symptoms at baseline. There were 416 (1.7%) incident cases of MDD during the 13-year follow-up. Modelled cross-sectionally, replacing 30 min/day of passive sedentary behaviour with 30 min/day of mentally active sedentary behaviour, light physical activity and moderate-to-vigorous activity reduced the odds of depression symptoms by 5% (odds ratio 0.95, 95% CI 0.94–0.97), 13% (odds ratio 0.87, 95% CI 0.76–1.00) and 19% (odds ratio 0.81, 95% CI 0.93–0.90), respectively. Modelled prospectively, substituting 30 min/day of passive with 30 min/day of mentally active sedentary behaviour reduced MDD risk by 5% (hazard ratio 0.95, 95% CI 0.91–0.99); no other prospective associations were statistically significant. Conclusions: Substituting passive with mentally active sedentary behaviours, light activity or moderate-to-vigorous activity may reduce depression risk in adults.